2019
DOI: 10.1002/btpr.2860
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and bioleaching of nickel laterite ore using Bacillus subtilis strain

Abstract: There are two principal types of nickel (Ni) deposits: sulfide and laterite ores. Interest in low‐grade Ni‐laterite ores has increased in recent years as high‐grade Ni‐sulfide deposits are being quickly depleted. However, processing of Ni laterites has proven technically difficult and costly, and the development of alternative low‐cost biotechnologies for Ni solubilization has been encouraged. In this context, by the first time, a sample of Brazilian Ni‐laterite ore was analyzed mineralogically and subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…An alternative explanation could be a chemical effect of cell exudates, such as ligands that retarded leaching or the solubility of REEs. However, despite its previously demonstrated bioleaching activity 45,46 , and cell wall absorption of REEs 47 , Kucuker et al 48 showed that B. subtilis was not able to extract tantalum, a transition metal considered similar to a REE, from capacitors.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation could be a chemical effect of cell exudates, such as ligands that retarded leaching or the solubility of REEs. However, despite its previously demonstrated bioleaching activity 45,46 , and cell wall absorption of REEs 47 , Kucuker et al 48 showed that B. subtilis was not able to extract tantalum, a transition metal considered similar to a REE, from capacitors.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kucuker et al (2019) showed that B. subtilis was not able to extract tantalum from capacitors. However, the organism has previously been shown to enhance the bioleaching of copper and nickel by producing a lipoprotein that binds to the copper or nickel in the supernatant ( Rozas et al, 2017 ; Giese et al, 2019 ) and the binding of rare earth elements to the cell wall ( Takahashi et al, 2005 ) suggests cell wall-binding as one mechanism of leaching.…”
Section: Discussionmentioning
confidence: 99%
“…Among the microorganisms that showed a higher resistance to space radiations we can find Chrooccocidiopsis (Cockell et al 2005;Billi et al 2019), Bacillus subtilis (Moeller et al 2014;Ulrich et al 2018;Nicholson and Ricco 2020) and Deinococcus radiodurans (Mattimore and Battista 1996;Minton 1996), and some fungi as Aspergillus niger (Cortesão et al 2020). Many of these have been also tested for their biomining (Brandl et al 1999;Rozas et al 2017;Faraji et al 2018;Giese et al 2019) or biosorption (Liu et al 2012;Jaafar et al 2015) capacity, suggesting a possible role for biomining in space. It must be noted that some of the molecular mechanisms of radiation (and related stresses) tolerance require the entrance of the cell in a dormant state (e.g., endospore formation, desiccation).…”
Section: Space Conditions and Effects On Biominingmentioning
confidence: 99%
“…Bacterial species include Acinetobacter, Pseudomonas and Bacillus spp. (Reed et al 2016;Rozas et al 2017;Barnett et al 2018;Giese et al 2019). Brisson and colleagues (Brisson et al 2020) recently performed a thorough metabolomic study which suggested that bioleaching of a given element could be mediated by specific organic acids, rather than organic acids in general.…”
Section: Organotroph Microorganismsmentioning
confidence: 99%